(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Currently, bulky formations of the uterus and uterine appendages are a chastopathology found in women of late reproductive, premenopausal and postmenopausal age. In patients with tumors of the uterus and uterine appendages, it is very difficult to differentiate the nature of the tumor process by clinical signs, since the symptoms (pelvic pain, menstrual dysfunction, infertility) are characteristic of inflammatory ovarian formations, endometrioid or dermoid ovarian cysts. Bimanual and rectovaginal examination do not always reveal the true localization of the formation (ovary, retroperitoneal tumor, intestine), its size, boundaries, and relationships with adjacent organs. In this regard, additional research methods are used for the differential diagnosis of tumors of the pelvic organs: echography, computed tomography, magnetic resonance imaging, multispiral computer tomography and others, which allow changing the approach to the study of diseases of the female genital area and abandoning such techniques as artificial pneumoperitoneum, bicontral gynecology, reducing the number of radionuclide studies, angiography and diagnostic surgical procedures.